Xiao-Yao-San reduces blood-brain barrier injury induced by chronic stress in vitro and vivo via glucocorticoid receptor-mediated upregulation of Occludin. (10th January 2020) - Yu, Shaolong; Fu, Lijun; Lu, Jiandong; Wang, Zhiyu; Fu, Wenjun
Abstract: Blood-brain barrier (BBB) is a barrier which maintains the material exchange balance of brain microenvironment and could be destroyed by chronic stress (CS). Glucocorticoids (GCs) can mimic the chronic stress induced damage to BBB. GCs induced BBB trauma models in vitro and in vivo to explore the effects of the traditional medicine Xiao-Yao-San (XYS). In this research, we found CS could injure the BBB to change the biochemical index, which could be reversed by XYS in vitro . The abilities of cell proliferation, invasion, and the expression of tight junction related genes (Occludin, Claudin, JAM-1 and ZO-1) were suppressed by CS and the trauma could be reversed by XYS partly. It was showed that GRs interacted with Occludin directly and inhibited Occluding expression. In rats BBB trauma model, the GC content was deceased and BBB permeability was repaired by XYS. The expression of Occludin, Claudin, JAM-1 and ZO-1 were increased in the treatment of XYS. In our research, it shown that XYS affect the content of the GC and GR which interacted with Occludin directly for the first time. In addition, we also found that XYS could reduce BBB injury induced by CS via GR in BBB model in vitro . Therefore, it proves that XYS is a potential BBB repair medicine and may help to elucidate mechanism of brain pathology. Graphical abstract: Image 1